Less invasive surfactant administration (LISA): chances and limitations - Herting, Egbert (Arch Dis Child Fetal Neonatal Ed, 2019)
Non-invasive ventilation and especially the application of continuous positive airway pressure (CPAP) has become standard for the treatment of premature infants with respiratory problems. However, CPAP failure may occur due to respiratory distress syndrome, that is, surfactant deficiency. Less invasive surfactant administration (LISA) aims to provide an adequate dose of surfactant while the infant is breathing spontaneously, thus avoiding positive pressure ventilation support. Using a thin catheter for surfactant application allows infants to maintain function of the glottis and continue spontaneous breathing, whereas the INtubate-SURfactant-Extubate (INSURE) procedure is connected with sedation/analgesia, regular intubation and a (brief) period of positive pressure ventilation. Individual studies and meta-analyses summarised in this review point in the direction that LISA is more effective than standard treatment or INSURE both in terms of short-term (avoidance of mechanical ventilation) and long-term (intracerebral haemorrhage and bronchopulmonary dysplasia) outcomes. Open questions include exact treatment thresholds for different gestational ages, the usefulness of devices/catheters that have recently been purpose-built for the LISA technique and especially the question of analgesia/sedation during the procedure. The current technology still demands laryngoscopy with all its unpleasant effects for infants. Therefore, studies with pharyngeal surfactant deposition immediately after delivery, the use of laryngeal airways for surfactant administration and attempts to nebulise surfactant are under way. Finally, LISA is not simply an isolated technical procedure for surfactant delivery but rather part of a comprehensive non-invasive approach supporting the concept of a gentle transition to the extrauterine world enabling preterm infants to benefit from the advantages of spontaneous breathing.